Interculturalidad en salud y eficacia: algunas indicaciones de uso para OGND con proyectos de salud en América Latina - Juan Antonio Flores Martos (Nuevo mundo - Mundos Nuevos, 2011)
This article presents a series of critical reflections on the concept of intercultural health, the discourse generated, and practices, or its lack in the NGOD, often located between the lack of cultural competence and intercultural rhetorical use in their actions and health programs. It intends to open a theoretical and critical discussion on intercultural health, from awareness of ts necessity and concern for their effectiveness. On the basis of an anthropological documentary, the author makes some proposals for better management of intercultural health. This is not limited to supposedly marginalized populations culturally but can extend to all users of biomedicine that are not in the too formal patient treatment, response to their problems.